Plasmodium UIS3 sequesters host LC3 to avoid elimination by autophagy in hepatocytes - Real, Eliana; Mair, Gunnar R. (Nature microbiology, 2018)
To evade autophagy-mediated killing when inside liver cells, the Plasmodium berghei protein UIS3 binds to a key regulator of the autophagy programme, the host protein LC3, and inhibits its interaction with downstream effectors.
Published online: 06 November 2017
Im Titel ist "Plasmodium" kursiv geschrieben
Gesehen am 23.04.2018